CBIR Approach Based On Combined HSV, Auto Correlogram, Color Moments and Gabor Wavelet (International Journal of Engineering and Computer Science, 2014)
Content  based  image  Retrieval  is  an  active  research field  in  past  decades.  Against  the  traditional  system where  the images  are  retrieved  based  on  the  keyword  search, CBIR  system retrieve  the  images  based  on  the  visual  content. The large numbers of images has posed increasing challenges to computer systems to store and manage data effectively and efficiently.  This  paper  implements  a  CBIR  system  using  different  feature  of images  through  four  different  methods,  three  were  based  on  analysis  of  color  feature  and  other  one based on analysis texture feature using gabor wavelet coefficients of an image.